Komunikasi Marketing Web Series Melalui Digital Traveloka - Eka Prastianto; Farhan Julian; Dini Safitri (Universitas Muhammadiyah Sidoarjo, 2019)
In the current era of modernization, many business people have begun to develop their businesses that were previously managed offline and are directed towards online management. Web series is a recent innovation in the field of advertising with the concept of serial promotion events released by various internet media, such as through YouTube, which is the main platform for web series production. Based on the data obtained by the use of web series on Youtube media is quite a lot even some have watched more than 1 million times. The author is interested in conducting research on web series, with the aim of researching how the web series is used as a digital marketing communication strategy on Traveloka. In conducting this research the writer uses descriptive qualitative research methods. The theory in this research is content marketing in web series, in building an awareness of an advertisement of a brand. The results of this study indicate that with the digital market online there are many positive sides to being closer to consumers and also faster in time, quickly promoting or introducing products to the public, the absence of market boundaries to reach all corners of the world connected to the internet, and accuracy and speed of service are the main needs of consumers in the era of globalization.